2017
DOI: 10.1002/ejoc.201700603
|View full text |Cite|
|
Sign up to set email alerts
|

Thiol–Yne Coupling of Propargylamine under Solvent‐Free Conditions by Bond Anion Relay Chemistry: An Efficient Synthesis of Thiazolidin‐2‐ylideneamine

Abstract: Thiol–yne coupling of propargylamine with isothiocyanate has been developed under metal‐ and solvent‐free conditions. The addition of propargylamine to isothiocyanate gives propargylthiourea. This intermediate in situ undergoes intramolecular 5‐exo‐dig cyclization to give thiazolidin‐2‐ylideneamine. A through‐bond anion relay reaction occurs by attack of the sulfur (not the nitrogen) atom on the alkyne in a highly regioselective manner at ambient temperature. Wide varieties of thiazolidin‐2‐ylideneamine deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 54 publications
5
19
0
Order By: Relevance
“…We found also that treatment of 19 with phenyl isothiocyanate in dichloromethane for 2 h at room temperature resulted in the formation of the thiazolidine 22a in good yield. This cyclization pathway appears to be general with amine 19 for the same types of isothiocyanates we have investigated previously delivering thiazolidines 22b–d (Table ) . While our own investigation was continuing, the Dethe lab reported that heating neat mixtures of propargylamines, including 19 , and an isothiocyanate does afford the corresponding thiazolidine, and we were able to reproduce this .…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…We found also that treatment of 19 with phenyl isothiocyanate in dichloromethane for 2 h at room temperature resulted in the formation of the thiazolidine 22a in good yield. This cyclization pathway appears to be general with amine 19 for the same types of isothiocyanates we have investigated previously delivering thiazolidines 22b–d (Table ) . While our own investigation was continuing, the Dethe lab reported that heating neat mixtures of propargylamines, including 19 , and an isothiocyanate does afford the corresponding thiazolidine, and we were able to reproduce this .…”
Section: Resultssupporting
confidence: 69%
“…This cyclization pathway appears to be general with amine 19 for the same types of isothiocyanates we have investigated previously delivering thiazolidines 22b–d (Table ) . While our own investigation was continuing, the Dethe lab reported that heating neat mixtures of propargylamines, including 19 , and an isothiocyanate does afford the corresponding thiazolidine, and we were able to reproduce this . However, the divergence in product formation between the two labs on reaction of propargylamine 19 and phenylisothiocyanate when conducted in solution was troubling and we wished to elucidate the source of the discrepancy.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…
The editorial office of the European Journal of Organic Chemistry (EurJOC) was informed by a reader on August 8th, 2017, that in the original article [1] the explanation of the mechanism as anion relay chemistry (ARC) was erroneous and the melting points of some of the compounds were reported in too wide ranges.We apologize for the confusion. The corrected Scheme 1 is given below.

We have also measured the melting points of all these compounds again, and the correct values are given below:

(133-135°C), 4q (121-123°C), 4s (compound decomposed at higher temperature; no proper m.

7057

We are thankful to Professor Carl J. Lovely, The University of Texas at Arlington, for pointing out that we confused resonance structures with ARC and for bringing the wide ranges of the melting points to our attention.

The Authors
…”
mentioning
confidence: 99%
“…The editorial office of the European Journal of Organic Chemistry (EurJOC) was informed by a reader on August 8th, 2017, that in the original article [1] the explanation of the mechanism as anion relay chemistry (ARC) was erroneous and the melting points of some of the compounds were reported in too wide ranges.…”
mentioning
confidence: 99%